Arginine supplementation improves lactate dehydrogenase levels in steady-state sickle cell patients: preliminary findings from Kinshasa, the Democratic Republic of Congo - Ngonde, Ange C. M.; Lukanu, Philippe N.; Mubiala, Ange; Aloni, Michel N. (Frontiers in Pain Research, 2024)
BackgroundSickle cell disease (SCD) disrupts oxygen transport due to the abnormal shape and rigidity of red blood cells, leading to hemolysis. Hemolysis, a major co-morbidity in SCD, is indicated by elevated levels of lactate dehydrogenase (LDH). Arginine depletion, which is essential for nitric oxide (NO) synthesis, contributes to various complications in SCD. L-arginine supplementation may increase NO levels and reduce oxidative stress. Research on its benefits in SCD, which is prevalent in sub-Saharan Africa, is limited. This study evaluates the effect of arginine supplementation on LDH levels in patients with steady state SCD.MethodsIn a retrospective study, we evaluated the effect of arginine supplementation on LDH levels in a cohort of 31 patients. We divided the study into three phases: pre-HU treatment, HU treatment, and combined HU and arginine supplementation.ResultsThe cohort had a median age of 12 years, ranging from 2 to 43 years. Throughout all three phases of the study, lactate dehydrogenase (LDH) levels were consistently above the established normal ranges, with elevations of 216.7%, 220.3% and 176.6% above the normative values for baseline, Phase 1 (HU) and Phase 2 (HU + Arg), respectively. Specifically, LDH levels were 649.7 ± 364.2 U/L in Baseline Phase, 661.6 ± 367 U/L in Phase 1, and 529.9 ± 346.3 U/L in Phase 2. When comparing these discrete study intervals, it is noteworthy that LDH levels were significantly lower in Phase 2 compared to the previous phases (p = 0.002).ConclusionPreliminary findings revealed a significant lower LDH levels among sickle cell patients receiving combined arginine supplementation and hydroxyurea (HU). Although these findings are promising, their credibility and applicability require further and more extensive research.